a study on bilingual policy in relation to the issue of changingthe medium of instuction at the junior secondary level - Parasivam, S.S. (My University, 2004)
Change over of the medium of instruction to S i n h a l a and Tamil in 1950s made provision to teach English as a compulsory second language. Even though E n g l i s h has been taught for around half a decade it has failed to improve the students language proficiency in speaking and written English. With the introduction of the mother tongue as a medium of instruction, the students from different ethnic communities were segregated to S i n h a l a and Tamil streams i n schools. The children of these communties were isolated. Hence there was no common medium to communicate with each other. Therefore the necessity arose to use a common language i n a l l activities. As a result the Amity Schools Project was started i n 2001 to build national unity. To build national u n i t y through learning a second language was identified by the Amity Schools Project which was later developed as a strategy i n terms of bilingual policy. The National Education Commission (2003) has introduced a bilingual policy in 2002 in Junior Secondary level. The main objective of the bilingual policy was claimed to acquire a level of English proficiency for higher education and career advancement. (N.E.C. Report, 2003). This study is to investigate, whether there is a bilingual policy in Junior Secondary level and to identify the features of bilingual programme that has been introduced i n S r i L a n k a . For the purpose of the study a survey was carried out i n four leading schools. The survey consists of one hundred and fifty two students who are i n Grade 8 English medium classes. Among the four schools, an indepth study was based in two schools. Nine teachers who teach i n Grade 8 English medium classes of these respective leading schools were also the participants of this study.